UJIAN UNTUK IMAN YANG SEJATI BERDASARKAN MATIUS 13:1-23; 13:36-43 - Astrid Maryam Yvonny Nainupu (SAINT PAUL'S REVIEW, 2022)
In its continuity to distinguish true faith and false faith in the christian life is not an easy thing to do. Therefore there needs to be a test of faith to prove the authenticity of one's faith. This study uses the biblical text's exposition approach to Matthew 13:36-43 by looking at the background and finding the meaning of the text. Researchers also use interpretations to get a clearer meaning and then the results are presented by describing what tests are effective in proving the authenticity of one's faith . The test is through hardship and fun. Whether in adversity one still believes and worships God and whether in pleasure one does not forget God